Mitigating the negative effects of retrieval stress on memory: an arousal reappraisal intervention. Issue 3 (16th March 2021) - Marr, Carey; Sauerland, Melanie; Otgaar, Henry; Quaedflieg, Conny W.E.M.; Hope, Lorraine
ABSTRACT: In a preregistered experiment, we examined the efficacy of arousal reappraisal as an intervention for reducing the negative effects of stress at retrieval on memory. Participants ( N = 177) were semi-randomly assigned to one of three conditions: a Stress-intervention condition, a Stress-placebo condition, and a No-stress-placebo control condition. Participants viewed four images of complex, mildly negatively valenced scenes. One day later, they received an arousal reappraisal intervention or placebo before exposure to a laboratory stressor (or a control version for the No-stress condition). Participants were then tested on their memory of the images using a free recall instruction and multiple-choice recognition questions. As expected, negative affect and blood pressure increased for the stress conditions but not the control condition. Contrary to our hypotheses, memory performance did not statistically significant differ between the Stress-placebo condition and the No-stress-placebo control condition, indicating a lack of negative effects of acute retrieval stress on memory. Furthermore, we also found no statistically significant differences between the Stress-intervention condition and Stress-placebo condition in terms of memory performance, suggesting that the intervention did not assist with enhancing memory. We integrate interpretations of the findings from this study with a discussion of avenues for future research in this area.